THE EFFECT OF THE APPLICATION OF THE INFORMATION SYSTEM OF THE REGIONAL GOVERNMENT OF THE REPUBLIC OF INDONESIA ON THE SATISFACTION OF USERS OF ACCOUNTING INFORMATION SERVICES AT THE OFFICE OF THE REGIONAL FINANCIAL AND ASSET AGENCY OF SIDENRENG RAPPANG D - Adith Fitra, Rifky; Kurniawan, Kurniawan; Rahman, Usman (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study is motivated by the transition of the use of the Regional Government Information System application and at the beginning of 2024 it became the Republic of Indonesia Regional Government Information System which has been implemented in all regions of the Republic of Indonesia. This study aims to determine the effect of the Republic of Indonesia local government information system (X) including content (X1), accuracy (X2), format (X3), ease of use (X4), and timeliness (X5) on user satisfaction of accounting information services (Y) at the Sidenreng Rappang Regency Regional Finance and Asset Agency office using the end-user computing satisfaction method as a tool to measure user satisfaction. The population in this study were civil servants in the scope of the office totaling 46 people and also the number was drawn into a sample in this study using a saturated sampling technique totaling 46 people who would be given a questionnaire. The analysis model used to prove the hypothesis is path analysis. The results showed that of the 46 respondents studied, of the 6 hypotheses proposed, 3 hypotheses were rejected and 3 hypotheses were accepted. Where the partially accepted variables are format (X3) and timeliness (X5), and the rejected variables are content (X1), accuracy (X2), and ease of use (X4). Simultaneously, the five variables are proven to simultaneously affect the user satisfaction variable (Y). Based on this, in order to develop in the academic field, it is hoped that further researchers will develop variables and increase the number of respondents for better results.